2018
DOI: 10.1017/s0022029918000742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymerized whey protein on goaty flavor and texture properties of fermented goat milk in comparison with β-cyclodextrin

Abstract: Goaty flavor and poor consistency may impact consumer acceptance of fermented goat milk. The undesirable characteristics can mainly be attributed to the presence of short-medium chain free fatty acid (SM-FFA) especially C6-C10 fatty acids and low αs1-casein content in goat milk. This study aimed to investigate the effects of polymerized whey protein (PWP) on goaty flavor as well as the texture properties of fermented goat milk in comparison with β-cyclodextrin (β-CD). Samples were evaluated on sensory properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…GMY samples were sensory evaluated according to the method of [26] modified by [27] for sensory properties (color, texture, flavor, and overall acceptability) using a 5-point hedonic scale, (1 = extremely dislike to 5 = extremely like). Ten expert panelists of Food Technology Research Institute members were recruited to make the sensory evaluation.…”
Section: Sensory Evaluation Of Gmymentioning
confidence: 99%
See 1 more Smart Citation
“…GMY samples were sensory evaluated according to the method of [26] modified by [27] for sensory properties (color, texture, flavor, and overall acceptability) using a 5-point hedonic scale, (1 = extremely dislike to 5 = extremely like). Ten expert panelists of Food Technology Research Institute members were recruited to make the sensory evaluation.…”
Section: Sensory Evaluation Of Gmymentioning
confidence: 99%
“…[45] Thus, goat milk texture, alongside the goaty flavor, represents the main defect that negatively influences its production and consumption. To overcome the less firm texture of GMY, increasing total solids, adding stabilizers such as pectin, [46] polymerized whey protein, Beta-cyclodextrin, [27] and microbial transglutaminase [9] were evaluated. Moreover, flours derived from the food of plant origin were added into goat milk to improve the microstructure and texture of its yogurt.…”
Section: Texture Characteristics Of Gmymentioning
confidence: 99%
“…Caprylic, capric, and caproic acids are wildly believed responsible for the flavor of goaty [5,6]. Thus, in order to overcome the defects of goat milk product in terms of sensory characteristics, researchers proposed the addition of β-cyclodextrins or polymerized whey protein to trap caprylic, capric, and caproic acids for reducing goaty flavor [7,8]. Fruit juice was also considered to add into goat milk product to bate or mask the goaty flavor [9].…”
Section: Introductionmentioning
confidence: 99%
“…The free fatty acids were encapsulated by β‐CD, and the sweetness of lactitol masked the bad flavor of goat milk. Relevant research showed that the combined addition of polymerized whey protein and β‐CD could relieve the goaty flavor and improve the texture of fermented goat milk 20 . The supplementation of inulin and β‐CD could improve the sensory acceptability and curdling properties of fermented goat milk 30 …”
Section: Resultsmentioning
confidence: 99%